EFEKTIVITAS PEMBERIAN SIMULASI HAND HYGIENE TERHADAP KEPATUHAN HAND HYGIENE PETUGAS NON MEDIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA UNIT II - Ekorini Listiowati; Lisa Nilamsari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Hospital Associated Infection (HAIs) is the world’s problem and one of the causes is hand hygiene compliance in healthcare workers are still low. Data showed 80% of HAIs spread by hands. Non medical healthcare workers are at risk for spreading the phatogen by hands, because although they don’t give intervention directly to the patients, they still have big possibilities to be in one of 5 moments hand hygiene. Hand hygiene simulation is one of training methods for heakthcare workers to create higher compliance in hand hygiene. This research was an experimental design with one group pre-posttest design. The population were all non medical healthcare workers in security department, nutritional department, and cleaning service department, the total sample is 37 persons. Paired T-test is used for stastitical analysis.The results obtained, the implementation of hand hygiene with proper procedure is 0,55%. The compliance rate increase after intervention by hand hygiene simulation 13,83%. Statistical analysis showed significant result p<0,05; p=0,026 for security department, p=0,027 for nutritional department, and p=0,002 for cleaning service department, meaning there is a difference in hand hygiene compliance of non medical healthcare workers before and after intervention by hand hand hygiene simulation.Hand hygiene simulation is effecticve to improve hand hygiene compliance. Therefore it can be used to improve hand hygiene compliance in non medical healthcare workers.